Stability of Recombinant Proteins in Escherichia coli: The Effect of Co-Expression of Five Different Chaperone Sets - H. Mirzahoseini (Journal of Sciences, Islamic Republic of Iran)
Chaperones are produced by prokaryotic, yeast and higher eukaryotic cells for various purposes. Over-expression of each chaperone or sets of them affect the production level of a recombinant protein in the cell. On the basis of this hypothesis, five different plasmids with 5 different combinations of 6 chaperones molecule, transformed into Escherichia coli along with human basic Fibroblast Growth Factor expression plasmid. Each transformant that contain both plasmids for expression of hbFGF and chaperone combinations was induced with proper concentration of related inducers. Subsequently, total amount of produced hbFGF was analyzed based on SDS-PAGE and ELISA. Our results indicated that “TF” and “DnaK/DnaJ/GrpE” destabilized hbFGF, while “DnaK/DnaJ/GrpE/GroEL /GroES” and “GroEL/GroES” combinations were able to stabilize it. It has also revealed that “GroEL/GroES/TF” combination negatively affected the hbFGF production.